2021
DOI: 10.1007/s10096-021-04152-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the vaginal microbiomes in prepubertal girls with and without vulvovaginitis

Abstract: The present study focused on the characteristics of the vaginal microbiomes in prepubertal girls with and without vulvovaginitis. We collected 24 vaginal samples and 16 fecal samples from 10 girls aged 3–9 years with vulvovaginitis and 16 healthy girls of the same age. The samples were divided into three groups: fecal swabs from healthy controls (HF), vaginal swabs from healthy controls (HVS), and vaginal swabs from girls with vulvovaginitis (VVS). Sequencing of the V3–V4 region of the 16S rDNA gene was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Culture and metagenomic approaches have identified a broad array of bacterial taxa in pediatric vaginal and male urine specimens. 82 , 83 , 84 , 85 , 86 , 87 However, few common patterns have emerged across these studies, and there seems to be general agreement that pediatric urogenital microbiomes are disorganized and sparse. By adolescence, unknown behavioral and/or developmental changes in male individuals permit prolonged colonization of the distal PU by core microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Culture and metagenomic approaches have identified a broad array of bacterial taxa in pediatric vaginal and male urine specimens. 82 , 83 , 84 , 85 , 86 , 87 However, few common patterns have emerged across these studies, and there seems to be general agreement that pediatric urogenital microbiomes are disorganized and sparse. By adolescence, unknown behavioral and/or developmental changes in male individuals permit prolonged colonization of the distal PU by core microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an early cultivation method study demonstrated that vaginal microbiota of prepubertal girls mainly consisted of Staphylococcus epididermis, Enterococci, Escherichia coli (aerobic microbe), Peptococcus , and Peptostreptococcus (anaerobic microbe) ( 29 ). A recent 16s rRNA sequencing study revealed the vaginal microbiome of healthy prepubertal girls was dominated by Prevotella, Porphyromonas , and Ezakiella ( 30 ). Similar to prepubertal period, vaginal glycogen levels in menopausal women are lower than in premenopausal women ( 31 ).…”
Section: Host Factors Determining Vaginal Microbial Communitymentioning
confidence: 99%
“…What is considered as normal vaginal flora at different age periods is still a matter of dispute, and different data can be found in the literature. The vaginal microbiome is complex, and the presence of potential pathogens does not necessarily imply that they are responsible for the infection [7][8][9]. As a result, vaginal cultures obtained from vulvovaginitis cases must be cautiously evaluated before deciding specific antibacterial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BV has been rarely reported in the literature as a cause of vulvovaginitis in girls, and it was not associated with sexual activity [ 13 , 27 ]. In a normal prepubertal vagina, lactobacilli are lacking and, along with different aerobic species, anaerobic bacteria can also be found [ 2 , 7 , 9 , 15 ]. McGreal and Wood reported increased anaerobes (51%) in prepubertal girls [ 21 ].…”
Section: Discussionmentioning
confidence: 99%